Kesadaran Hukum Pelaku Usaha atas Pendaftaran Merek Dagang: Tinjauan Hukum Ekonomi Syariah - Riskawati (Laskar Karya, 2025)
This study aims to analyze the level of legal awareness among business actors in registering their trademarks in the field of intellectual property at the Regional Office of the Ministry of Law and Human Rights of Southeast Sulawesi. Legal awareness in this context includes the understanding, attitudes, and behavior of business actors toward the importance of legal protection for trademarks. The research method used is a juridical-empirical approach, with data collected through interviews, observations, and documentation involving MSME actors and officials from the Regional Office. The findings reveal that the legal awareness of business actors in Kendari City remains low, as indicated by the limited number of registered trademarks. Several inhibiting factors were identified, including lack of legal knowledge, the perception that the registration process is complex and costly, and insufficient outreach from relevant institutions. On the other hand, business actors who have registered their trademarks reported clear benefits, such as legal protection, increased competitiveness, and business legitimacy. Therefore, continuous educational and participatory approaches, along with inter-agency collaboration, are essential to enhance the legal literacy of business actors regarding trademark registration.